2015
DOI: 10.1007/978-3-319-15675-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the Biodegradation of Glasses for Biomedical Applications Through Classical and Ab-initio Simulations

Abstract: The gradual dissolution of a glass in a living host determines the rate at which processes leading to tissue regeneration can occur, which is of crucial importance for the success of biomedical implants and scaffolds for tissue engineering based on the glass. In-situ radiotherapy applications are also affected-in an opposite way-by the rate at which the glass vector used to deliver radioisotopes will degrade in the bloodstream. This chapter illustrates how a combination of classical and ab-initio simulations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…These simulations showed that some of these strained surface sites resist hydrolysis long enough to nucleate calcium phosphate precursors, which will then protect them from further reactions [71]. The simulations also suggested that the higher stability of small rings on the bioactive than the pure silica surface is also due to the presence of more favorable absorption sites for water like modifier cations (Na and Ca) and non-bridging oxygens [9].…”
Section: Glass Surfacementioning
confidence: 87%
See 1 more Smart Citation
“…These simulations showed that some of these strained surface sites resist hydrolysis long enough to nucleate calcium phosphate precursors, which will then protect them from further reactions [71]. The simulations also suggested that the higher stability of small rings on the bioactive than the pure silica surface is also due to the presence of more favorable absorption sites for water like modifier cations (Na and Ca) and non-bridging oxygens [9].…”
Section: Glass Surfacementioning
confidence: 87%
“…Thus, in the last years a fervent computational research activity has been carried out with the aim of supporting in the interpretation of the experimental results. In particular, atomistic computer simulations have shown to provide a detailed picture of the glass structures, and precious information on the structure-properties relationships of complex glasses [5][6][7][8][9]. In fact, the structural and dynamical features that control dissolution and bioactivity cover length and time scales accessible to molecular dynamics (MD) simulations [10][11][12][13][14] Therefore, computational studies have now remarkably advanced the understanding of bioactive glasses, as documented by the numerous reviews and perspective articles published in recent years [9,10,12,13] This chapter reviews the recent efforts to uncover sound relationships among the structure of crucial components and the physico-chemical properties of silicate, phospho-silicate and phosphate glasses with potential bioactive properties.…”
Section: Introductionmentioning
confidence: 99%